Towards Consistency of Dynamic Models and Analysis of Timing Constraints - Küster, Jochen; Stroop, Joachim (Proceedings of 1st Workshop on Formal Design Techniques for Real-time Systems (satellite event of the UML 2000), York (UK))

Methodische Aspekte von Modellierungssprachen für nebenläufige Software - Mehner, Katharina; Schattkowsky, Tim (Proceedings of the 8th GROOM Workshop: Visuelle Verhaltensmodellierung verteilter und nebenläufiger Softwaresysteme (VVVNS 2000), Münster (Germany))
In den letzten Jahren ist ein deutlicher Trend zu verstärkt nebenläufiger Software festzustellen. Hierfür gibt es verschiedene Gründe, wie die rasante Verbreitung des Internets mit seinen Client/Server-Architekturen und die verstärkte Unterstützung nebenläufiger Programmierung in neuen Programmiersprachen wie z.B. Java. Softwareentwickler werden somit zunehmend mit dem Problem der Synchronisation der nebenläufigen Abläufe in der Software konfrontiert. Dabei treten immer wieder gravierende Fehler auf. Besonders problematisch ist in diesem Zusammenhang der Nichtdeterminismus nebenläufiger Abläufe, der dazu führt, dass Fehler unter Umständen bei Tests nicht auffällig werden, weil das Auftreten der Fehler von einem bestimmten Zeitverhalten abhängt, das beim Test nicht auftritt. Die Situation wird noch erschwert, wenn man nebenläufige Software aus Komponenten verschiedener Hersteller zusammensetzt. Bei der Zusammenarbeit dieser Komponenten auftretende Fehler im nebenläufigen Ablauf sind besonders schwierig zu diagnostizieren und zu beheben, da über die verwendeten Komponenten meist nichts außerhalb ihrer nicht notwendigerweise vollständigen und korrekten Spezifikation bekannt ist. Dies ist ein aktuelles Problem, da Komponententechnologien den Kern vieler moderner Anwendungen bilden. Viele Fehler in nebenläufiger Software sind auf grundsätzliche Fehler beim Entwurf der Software zurückzuführen. Auch beim Übergang vom Modell zur Implementierung entstehen Fehler, insbesondere wenn das Modell nicht direkt bei der Implementierung umsetzbar ist. Dies ist häufig der Fall, weil die Implementierung meist auf der Verwendung einfacher Synchronisationskonstrukte, wie z.B. Semaphoren, basiert, welche in der verwendeten Modellierung kein direktes Gegenstück haben. Es ist also entscheidend, dass die Softwareentwickler beim Entwurf ein klares Bild von der zu entwickelnden Software erhalten, welches leicht in der Implementierung umzusetzen ist. Wir wollen im folgenden grundlegende Strukturen nebenläufiger Softwaresysteme aufzeigen, basierend darauf Anforderungen an Modellierungssprachen für solche Systeme formulieren und existierende Modellierungssprachen auf diese Anforderungen hin untersuchen. Dabei werden wir sehen, dass sich in diesen Systemen kleinere, nahezu in sich abgeschlossene, Abläufe identifizieren lassen, die wir als Operationen bezeichnen werden. Betrachtet man die Implementation so ist festzustellen, dass hier einige einfache Konstrukte im Vordergrund stehen, auf die das Modell abgebildet werden muss. Damit ergeben sich aus unserer Sicht zwei wesentliche Forderungen an Modellierungssprachen: · Die Aufteilung in einzelne Operationen soll gefördert werden. · Gängige Synchronisationskonstrukte sollen direkt dargestellt werden, um die Lesbarkeit der Darstellung zu verbessern und um den Übergang in die Implementierung zu vereinfachen. Im nächsten Abschnitt werden wir die grundlegende Struktur nebenläufiger Software beschreiben, bevor wir dann Anforderungen diskutieren. Wir werden State Charts als eine gebräuchliche Modellierungssprache hinsichtlich dieser Anforderungen untersuchen und dabei sehen, dass diese den Forderungen nicht vollständig gerecht werden. Dies wird an einem Beispiel vertieft. Abschließend gehen wir kurz auf den Übergang von der Modellierung in die Implementierung ein.

Visualisierung der Synchronisation von Java-Threads mit UML - Mehner, Katharina; Wagner, Annika (Proceedings of the Workshop on Modelle und Modellierungssprachen in Informatik und Wirtschaftsinformatik (Modellierung 2000), St. Goar (Germany))

Informatik '99: Informatik überwindet Grenzen. Tagungsband der 29. Jahrestagung der Gesellschaft für Informatik, Paderborn (Germany)

Patterns as a Means for Intelligent Software Engineering - Deugo, Dwight; Küster, Jochen; Oppacher, Franz; von Otte, Ingo (Proceedings of the conference on Artificial Intelligence (IC-AI 1999) Las Vegas, Nevada (USA))

Tile Transition Systems as Structured Coalgebras - Corradini, Andrea; Heckel, Reiko; Montanari, Ugo (Proceedings of the 12th International Symposium on Fundamentals of Computation Theory (FCT '99))

Application of the Structured Analysis and Design Technique (SADT) Methodology for the Medical Information Systems Development - Cherchago, Alexey (Proceedings of the All-Russia Students’, Young Scientists’ and Specialists’ Scientific and Technical Conference "New Information Technologies in Scientific Researches and in Education" (Ryazan, Russia))

Konzeption und objektorientierte Realisierung einer internet-basierten Datenbankanwendung - Engels, Gregor; Depke, Ralph; Borowski, Christoph (Kolloquium Software-Entwicklung - Methoden, Werkzeuge, Erfahrungen)
Today e-commerce applications use web browsers as an uniform user interface and they rely on databases as data sources. Different technologies exist for database access: common gateway interface (CGI), Java and its database interface java database connectivity (JDBC), proprietary approaches of database vendors, etc. We present criteria for the selection of an appropriate solution and we successivly apply them in our application development process. Throughout the development process of internet based database applications object oriented techniques can be used. The unified modeling language (UML) is used for requirement analysis and design of the application and the implementation proceeds with the programming language Java. The transition from the object oriented modeling language UML to the object oriented programming language Java succeeds smoothly. We report on our experience with the modeling tool Rational Rose 98 of Rational, Inc. We use Java and JDBC to implement a seminar reservation system that can be regarded as a small e-commerce application.

UML Collaboration Diagrams and Their Transformation to Java - Engels, Gregor; Hücking, Roland; Sauer, Stefan; Wagner, Annika (Proceddings of The Unified Modeling Language: Beyond the Standard, Second International Conference (UML 99), Fort Collins, Colorado, USA)

A Bi-Categorical Axiomatisation of Concurrent Graph Rewriting - Gadducci, Fabio; Heckel, Reiko; Llabrés, Mercé (Proceedings of the 8th Conference on Category Theory and Computer Science (CTCS 1999), Edinburgh (UK))
In this paper the concurrent semantics of double-pushout (DPO) graph rewriting, which is classically defined in terms of shift-equivalence classes of graph derivations, is axiomatised via the construction of a free monoidal bi-category. In contrast to a previous attempt based on 2-categories, the use of bi-categories allows to define rewriting on concrete graphs. Thus, the problem of composition of isomorphism classes of rewriting sequences is avoided. Moreover, as a first step towards the recovery of the full expressive power of the formalism via a purely algebraic description, the concept of disconnected rules is introduced, i.e., rules whose interface graphs are made of disconnected nodes and edges only. It is proved that, under reasonable assumptions, rewriting via disconnected rules enjoys similar concurrency properties like in the classical approach.

Modeling Agent-Based Systems with Graph Transformation and UML - Heckel, Reiko (Proceedings of the Dagstuhl-Seminar 99451 on Rigorous Analysis and Design for Software Intensive Systems)

Extending UML for Modeling of Multimedia Applications - Sauer, Stefan; Engels, Gregor (Proceedings of the IEEE Symposium on Visual Languages (VL 1999), Tokyo (Japan))
An analysis of how visual modeling of structure and dynamic behavior of a multimedia application differs from modeling conventional software yields that aspects of the graphical user interface and time-dynamic behavior ought to be integral parts of a coherent multimedia application model. In this sense, we extend the model-view-controller paradigm towards multimedia.As a result, we present OMMMA-L, a visual Language for the Object-Oriented Modeling of MultiMedia Applications that is based on the Unified Modeling Language (UML). The structural and behavioral diagram types of UML have been analyzed and are adapted and extended according to multimedia application characteristics.A presentation diagram is introduced and integrated to adequately describe the visual presentation. In addition to explaining the different diagram types, we also give pragmatic guidelines on how to deploy and combine the various diagrams.

Basic Properties of Double Pullback Graph Transitions - Ehrig, Hartmut; Heckel, Reiko; Llabrés, Mercé; Orejas, Fernando

UML Collaboration Diagrams and Their Transformation to Java - Engels, Gregor; Hücking, Roland; Sauer, Stefan; Wagner, Annika

SOCCA Extended with UML like Packages - Engels, Gregor; Jan t'Hoen, Pieter; Dassen, Ray; Groenewegen, Luuk; G. Sprinkhuizen-Kuyper, Ida; Koopman, Pieter

A Formalisation of SOCCA using Z, part 1: The Type Level Concepts - Engels, Gregor; Dassen, Ray; Groenewegen, Luuk; G. Sprinkhuizen-Kuyper, Ida; Koopman, Pieter; Jan t'Hoen, Pieter
This document starts the formalisation of the modelling language of the SOCCA OO method in the formal specification language Z. It captures the `static' aspects of SOCCA, i.e. the meaning of SOCCA language elements at the type level, rather than `dynamic' aspects (dealing with the instance level (objects in execution)). It is restricted to core SOCCA; proposed extensions are not formalised.

UML-basierte Modellierung von Multimediaanwendungen - Sauer, Stefan; Engels, Gregor (Modellierung 1999, Workshop der Gesellschaft für Informatik e. V. (GI), März 1999 in Karlsruhe)
Der Entwicklungsprozeß von Multimediaanwendungen sollte ebenso wie der herkömmlicher Softwaresysteme eine Analyse und einen Entwurf beinhalten. In dieser Arbeit diskutieren wir, inwiefern die Modellierung der Struktur und des dynamischen Verhaltens einer Multimediaanwendung über die Modellierung herkömmlicher Software hinausgeht. Wir zeigen, daß Aspekte der Benutzungsschnittstelle und das Zeitverhalten integraler Bestandteil der Modellierung sein sollten. Als Ergebnis stellen wir die objektorientierte Modellierungssprache OMMMA-L vor, die auf der Unified Modeling Language (UML) aufbaut. Die Struktur- und Verhaltensdiagramme von UML wurden analysiert und gemäß der Charakteristika von Multimedia adaptiert bzw. erweitert. Im Klassendiagramm werden die Medientypen und die logische Struktur der Anwendung modelliert. Als Verhaltensdiagramme werden spezialisierte Sequenz- und Zustandsdiagramme eingesetzt. Mit dem Layoutdiagramm wird ein neuer Diagrammtyp hinzugefügt, der die integrierte und anschauliche Beschreibung der visuellen Darstellung und interaktiver Benutzereingaben einer Multimediaanwendung erlaubt. Neben der Vorstellung der einzelnen Diagrammtypen geben wir ein aus dem Metamodell zu UML abgeleitetes OMMMA-L-Metamodell an, in dem das Zusammenspiel der Modellelemente aus den verschiedenen Diagrammen spezifiziert wird.

OMMMA: An Object-Oriented Approach for Modeling Multimedia Information Systems - Sauer, Stefan; Engels, Gregor (Proceedings of the workshop on Multimedia Information Systems (MIS 1999), Indian Wells, CA (USA))
We present an object-oriented approach based on the Unified Modeling Language (UML) for modeling structure and dynamic behavior of a multimedia information system. We extend the Model-View-Controller paradigm for interactive systems towards multimedia and show that aspects of the graphical user interface and time-dynamic behavior ought to be integral parts of a model. This is done in the intention of achieving a coherent model of a multimedia information system. As a result, we present OMMMA-L a UML-based language for the Object-Oriented Modeling of MultiMedia Applications. OMMMA-L deploys class and state diagrams of UML as well as an extended sequence diagram and a newly introduced presentation diagram to adequately specify the visual presentation within a multimedia information system. In addition to explaining the different diagram types, we also define pragmatic rules on how to deploy and combine the various diagrams. Additionally, we relate OMMMA-L to basic ideas of multimedia information systems.

An Algebra of Graph Derivations using Finite (co-) limit Double Theories - Corradini, Andrea; Große-Rhode, Martin; Heckel, Reiko (Selected papers of the 13th International Workshop on Recent Trends in Algebraic Development Techniques (WADT 1998), Lisbon (Portugal))

From SOS Specifications to Structured Coalgebras: How to Make Bisimulation a Congruence - Corradini, Andrea; Heckel, Reiko; Montanari, Ugo (Proceedings of the 2nd workshop on Coalgebraic Methods in Computer Science (CMCS 99))

Dynamic Meta Modelling: A Graphical Approach to Operational Semantics - Engels, Gregor; Heckel, Reiko; Sauer, Stefan (Proceedings of the workshop on Rigorous Modeling and Analysis with the UML: Challenges and Limitations (satellite event of the Conference on Onject-Oriented Programming, Systems, Languages, and Applications (OOPSLA 1999)), Denver, CO (USA))
In this paper, dynamic meta modeling is proposed as a new approach to the operational semantics of behavioral UML diagrams. The dynamic meta model extends the well-known static meta model by a specification of the system’s dynamics by means of collaboration diagrams. In this way, it is possible to define the behavior of UML diagrams within UML. The conceptual idea is inherited from Plotkin’s structured operational semantics (SOS) paradigm, a style of semantics specification for concurrent programming languages and process calculi: Collaboration diagrams are used as deduction rules to specify a goal-oriented interpreter for the language. The approach is exemplified using a fragment of UML statechart and object diagrams. Formally, collaboration diagrams are interpreted as graph transformation rules. In this way, dynamic UML semantics can be both mathematically rigorous so as to enable formal specifications and proofs and, due to the use of UML notation, understandable without prior knowledge of heavy mathematic machinery. Thus, it can be used as a reference by tool developers, teachers, and advanced users.

MVC-Based Modeling Support for Embedded Real-Time Systems - Engels, Gregor; Sauer, Stefan (Proceedings of OMER Workshop, Herrsching, Germany)
Several software architecture paradigms have been proposed for the development of interactive software systems and applications. Their common idea is the separation of user interface components from application logic. Normally, they are deployed as design patterns or basic frameworks of interactive systems. Deploying these architecture paradigms for multimedia systems or embedded real-time systems, first requires an appropriate adaption to the specific aspects of these application areas. We will compare within this position paper two well-known architecture paradigms and motivate an advanced architecture paradigm applicable to real-time, embedded multimedia systems. In addition, we will discuss that the architecture paradigm should be reflected within the structure of a modeling language.

An Assessment of Aspect Language Design - Mehner, Katharina; Wagner, Annika (Proceedings of the Young Researchers Workshop (satellite event of the Generative and Component-Based Software Engineering (GCSE 1999)), Erfurt (Germany))

On the Role of Method Families in Aspect Oriented Programming - Mehner, Katharina; Wagner, Annika (Proceedings of the ECOOP Workshop on Aspect Oriented Programming, Lisboa (Spain))

Ein Vorgehensmodell für die Multimedia-Entwicklung mit Autorensystemen - Depke, Ralph; Engels, Gregor; Mehner, Katharina; Sauer, Stefan; Wagner, Annika (Informatik Forschung und Entwicklung)
Multimedia-Anwendungen sind interaktive Softwaresysteme und verlangen als solche, mit softwaretechnischen Methoden erstellt zu werden. Sie werden heutzutage in der Regel mit Hilfe von Autorensystemen entwickelt, die eine Ad-hoc-Entwicklung auf Implementierungsniveau unterstützen. Hierdurch und wegen des Fehlens etablierter Vorgehensmodelle für die Multimedia-Softwareentwicklung reduziert sich der Multimedia-Entwicklungsprozeß auf die Implementierungsphase. Dies führt zu den in der Softwaretechnik bekannten Problemen wie mangelnder Konzeption und fehlender Dokumentation. Wir stellen in diesem Beitrag ein Vorgehensmodell für die Entwicklung von Multimedia-Anwendungen vor, in dessen Mittelpunkt eine Analyse- und Entwurfsphase im Hinblick auf eine Implementierung der Multimedia-Anwendung mit einem Autorensystem stehen. Ausgehend von einem frameworkbasierten Analysemodell der Anwendung und einem Modell der Realisierungsmöglichkeiten mit einem konkreten Autorensystem wird systematisch ein Implementierungsmodell auf Instanzebene abgeleitet, das als Eingabe für das Autorensystem verwendet wird. Das postulierte Vorgehensmodell wird exemplarisch für das Autorensystem Director am Beispiel der Domäne multimedialer Lehr-/Lernanwendungen erläutert.

Formalization of the development process for a software-hardware reflexodiagnostic tool - Cherchago, Alexey; Finaev, V. (Scientific bulletin of Academy of Information Technologies in Education, Science and Balneology)

Graph Transformation for Specification and Programming - Andries, Marc; Engels, Gregor; Habel, Annegret; Hoffmann, Berthold; Kreowski, Hans-Jörg; Kuske, Sabine; Plump, Detlef; Schürr, Andy; Taentzer, Gabriele (Science of Computer Programming)
The framework of graph transformation combines the potentials and advantages of both, graphs and rules, to a single computational paradigm. In this paper we present some recent developments in applying graph transformations as a rule-based framework for the specification and development of systems, languages, and tools. After reviewing the basic features of graph transformation, we discuss a selection of applications, including the evaluation of functional expressions, the specification of an interactive graphical tool, an example specification of abstract data types, and the definition of a visual database query language. The case studies indicate the need for suitable structuring principles which are independent of a particular graph transformation approach. To this end, we present the concept of a transformation unit, which allows systematic and structured specifications and programming based on graph transformation.

Handbook of Graph Grammars and Computing by Graph Transformation: Vol. 2: Applications, Languages, and Tools - Ehrig, Hartmut; Engels, Gregor; Kreowski, Hans Jörg; Rozenberg, Grzegorz
Graph grammars originated in the late 60s, motivated by considerations about pattern recognition and compiler construction. Since then, the list of areas which have interacted with the development of graph grammars has grown quite impressively. Besides the aforementioned areas, it includes software specification and development, VLSI layout schemes, database design, modeling of concurrent systems, massively parallel computer architectures, logic programming, computer animation, developmental biology, music composition, visual languages, and many others. The area of graph grammars and graph transformations generalizes formal language theory based on strings and the theory of term rewriting based on trees. As a matter of fact, within the area of graph grammars, graph transformation is considered as a fundamental computation paradigm where computation includes specification, programming, and implementation. Over the last three decades, graph grammars have developed at a steady pace into a theoretically attractive and important-for-applications research field. Volume 2 of the indispensable Handbook of Graph Grammars and Computing by Graph Transformations considers applications to functional languages, visual and object-oriented languages, software engineering, mechanical engineering, chemical process engineering, and images. It also presents implemented specification languages and tools, and structuring and modularization concepts for specification languages. The contributions have been written in a tutorial/survey style by the top experts in the corresponding areas. This volume is accompanied by a CD-Rom containing implementations of specification environments based on graph transformation systems, and tools whose implementation is based on the use of graph transformation systems.

A View-based Approach to System Modeling Based on Open Graph Transformation Systems - Heckel, Reiko; Engels, Gregor; Ehrig, Hartmut; Taentzer, Gabriele (Handbook of Graph Grammars and Computing by Graph Transformations, Volume 2: Applications, Languages and Tools)
The idea of a combined reference model- and view-based specification approach has been proposed recently in the software engineering community. In this chapter we present a specification technique based on open graph transformation systems (in the double-pushout approach) by a new loose semantics for rule-based systems, which allows to model the interaction between different views, and by explicit frame conditions which restrict these interactions to an interface of open types. On this background, formal notions of view and view relation are developed and the behavior of views is described by the loose semantics. Based on the assumption that dependencies between different views are faithfully described by a common reference model, a construction is developed for the automatic integration of views. The views and the reference model are kept consistent manually, which is the task of a model manager. All concepts and results are illustrated at the well-known example of banking system.

Classification and Comparison of Module Concepts for Graph Transformation Systems - Heckel, Reiko; Engels, Gregor; Ehrig, Hartmut; Taentzer, Gabriele (Handbook of Graph Grammars and Computing by Graph Transformations, Volume 2: Applications, Languages and Tools)
In this chapter we use a three-level approach for analyzing module concepts for graph transformation systems. Based on the observation that module architectures consist of basic specications like body or export interface and relations like the implementation relation between them, or the import relation between a client and a server module, module concepts are characterized by answering the questions 1. What are the basic specifications? 2. Which relations between specifications are used? 3. How are specifications and relations combined to module architectures? These three questions are investigated for five module concepts available in the literature. As a reference example, a samplemodular specification of resource management in distributed operating systems is presented.

Semi-Formal and Formal Specification Techniques
During the last 20 years several different formal and semi-formal specification techniques have been successfully developed and used. Applications comprise the specification of simple programs, data types and processes as well as complex hardware and software systems. The variety of specification techniques ranges from formal set theoretical, algebraic, and logic approaches for specifying sequential systems and from Petri-nets, process algebras, automata, and graph grammars for specifying concurrent and distributed behaviors to semi-formal software engineering methods for developing complex systems. Formal and semi-formal approaches have their advantages and disadvantages: the informal diagrammatic methods are easier to understand and to apply but they can be ambiguous. Due to the different nature of the employed diagrams and descriptions it is often difficult to get a comprehensive view of all functional and dynamic properties. On the other hand, the formal approaches are more difficult to learn and require mathematical training. But they provide mathematical rigor for analysis and prototyping of designs. Verification is possible only with formal techniques. Since a few years many researchers and research groups are putting more and more effort in closing this gap by integrating semi-formal and formal specification techniques. Their studies and experiences show the added value of combining semi-formal and formal techniques and at the same time open a whole range of new problems and questions which cannot be asked when studying formalisms in isolation. In this seminar more than 40 scientists came together in 28 talks and two panel discussions to study possibilities and solutions for integrating and validating different formal and semi-formal specification techniques. Similarities and differences of formal and semi-formal specification formalisms as well as possibilities for combining such techniques were discussed. Most talks of this seminar analysed, compared, or integrated at least two such methods. On behalf of all participants the organizers would like to thank the staff of Schloss Dagstuhl for providing an excellent environment to the conference. The support of the TMR programme of the European Community is gratefully acknowledged. Due to this programme it was possible to fund the participation of several young researchers and of three key note speakers.

6th International Workshop on Theory and Applications of Graph Transformations (TAGT '98), Paderborn, Selected Papers

Ein Ansatz zur Verbesserung des Entwicklungsprozesses von Multimedia-Anwendungen - Depke, Ralph; Engels, Gregor; Mehner, Katharina; Sauer, Stefan; Wagner, Annika (Proceedings of the GI-Fachtagung on Softwaretechnik (1998), Paderborn (Germany))

Integration of Single Pushout Transformation and Functional Programming - Didrich, Klaus; Wagner, Annika (Proceedings of the World Conference on Integrated Design and Process Technology (IDPT 1998), Berlin (Germany))

A generalized schema of a decision-making process of a SCENAR-therapeutist - Cherchago, Alexey (Proceedings of the Scientific and Technical Conference on Medical Information Systems (MIS 1998), Taganrog (Russia))

Compositional Verification of Reactive Systems Specified by Graph Transformation - Heckel, Reiko (Proceedgins of the First International Conference on Fundamental Approaches to Software Engineering (FASE 1998), Lisbon (Portugal))

Interoperability in Train Control Systems: Specification of Scenarios Using Open Nets - Padberg, Julia; Jansen, Lars; Heckel, Reiko; Ehrig, Hartmut (Proceedings of the conference on Integrated Design and Process Technology (IDPT 1998), Berlin (Germany))

Electronic Commerce Systeme als Anwendungsbeispiel für Evolutionstechniken - Engels, Gregor; Kolmschlag, Silvia

Unterstützung der Flexibilität eines Electronic Commerce Systems durch Evolutionstechniken - Kolmschlag, Silvia; Engels, Gregor (Proceedings of the workshop on "Integration heterogener Softwaresysteme" (satellite event of the GI-Jahrestagung Informatik 1998), Magdeburg (Germany))

Structured Transition Systems as Lax Coalgebras - Corradini, Andrea; Große-Rhode, Martin; Heckel, Reiko (Proceedings of the First Workshop on Coalgebraic Methods in Computer Science (CMCS 1998), Lisbon (Portugal))

Simple Modules for Grace - Heckel, Reiko; Hoffmann, Berthold; Knirsch, Peter; Kuske, Sabine (Selected papers of the 6th International Workshop on Theory and Application of Graph Transformation (TAGT 1998), Paderborn (Germany))

Graph Transformation and Other Rule-Based Formalisms with Incomplete Information - Ehrig, Hartmut; Heckel, Reiko; Padberg, Julia; Rozenberg, Grzegorz (Proceedings of the 6th International Workshop on Theory and Application of Graph Transformation (TAGT 1998), Paderborn (Germany))
A general framework is presented for extending graph transformation and other rule-based formalisms in such a way that transformations with incomplete information can be handled. This extension is motivated by the need to model the behaviour of open systems in different application areas using graph transformations and Petri nets. The following two problems are central within this general framework. 1. Characterization of transformations with incomplete information. 2. Recovery of information from incomplete transformations. A solution for these problems is presented for algebraic graph transformations and Petri nets using the new concepts of graph transitions based on double pullbacks and open nets based on autonomous actions for open places. Moreover, the problems are discussed for DNA-computing and other rule-based formalisms.

Double-Pullback Graph Transitions: A Rule-Based Framework with Incomplete Information - Ehrig, Hartmut; Heckel, Reiko; Llabrés, Mercé; Orejas, Fernando; Padberg, Julia; Rozenberg, Grzegorz (Selected papers from the 6th International Workshop on Theory and Application of Graph Transformations (TAGT 1998), Paderborn (Germany))

Classification and Comparison of Modularity Concepts for Graph Transformation Systems - Ehrig, Hartmut; Engels, Gregor; Heckel, Reiko; Taentzer, Gabriele (Pre-Proceedings of the 6th International Workshop on Theory and Application of Graph Transformation (TAGT '98), Paderborn (Germany))
This paper presents a systematic approach for classifying and comparing modularity concepts that have been proposed for graph transformation systems. The approach is based on the following observation: Modules and module interconnections consist of basic specifications (forming, e.g., a module's body, import, or export interface), and relations between such specifications, like the implementation relation between export and body of a module. Hence, a natural approach for characterizing a module concept is to answer the following three questions: 1. What are the basic specifications? 2. Which relations between specifications are used? 3. How are specifications and relations combined to modules and interconnections? In this paper, these questions are considered in some detail for the following module concepts for graph transformation systems.

Model Checking Graph-Interpreted Temporal Formulas - Gadducci, Fabio; Heckel, Reiko; Koch, Manuel (Proceedings of the 6th International Workshop on Theory and Application of Graph Transformation (TAGT 1998), Paderborn (Germany))

DPO Derivations via Disconnected Rules - Gadducci, Fabio; Heckel, Reiko; Llabrés, Mercé (Proceedings of the 6th International Workshop on Theory and Application of Graph Transformation (TAGT 1998), Paderborn (Germany))

Event Processing in Mobile and Active Database Systems Using Broadcasts - Sauer, Stefan; Zukunft, Olaf (Proceedings of the 9th International Workshop on Database and Expert Systems Applications (DEXA 1998), Vienna (Austria))
The integration of active database technology into mobile database systems allows to limit the transfer of data between mobile computers and the stationary network. In order to employ such active database mechanisms, the rule processing component of traditional active database systems needs to be modified. This paper introduces a new model for event processing and presents a new algorithm for the composition of complex events in a mobile database environment. Furthermore, the model also takes into account the possibility of broadcast data. To validate the feasibility of the model, a prototype has been built using object-oriented technology.

Construction and Characterisation of Double-Pullback Graph Transitions - Ehrig, Hartmut; Heckel, Reiko; Llabrés, Mercé; Orejas, Fernando (Proceedings of the 6th International Workshop on Theory and Application of Graph Transformation (TAGT 1998), Paderborn (Germany))

Open Graph Transformation Systems: A New Approach to the Compositional Modelling of Concurrent and Reactive Systems - Heckel, Reiko

Themenheft: Softwaretechnik

A View-Oriented Approach to System Modelling Using Graph Transformations - Engels, Gregor; Heckel, Reiko; Taentzer, Gabriele; Ehrig, Hartmut (Proceedings European Software Engineering Conference (ESEC 1997), Zürich (Switzerland))
The idea of a combined reference model- and view-based specification approach has been proposed recently in the software engineering community. In this paper we present a specification technique based on graph transformations which supports such a development approach. The use of graphs and graph transformations supports an intuitive understanding and an integration of static and dynamic aspects on a well-defined semantical base. On this background, formal notions of view and view relation are developed and the behaviour of views is described by a loose semantics. We define a construction for automatic view integration which assumes that the dependencies between different views are described by a reference model. The views and the reference model are kept consistent manually, which is the task of a model manager. All concepts and results are illustrated at the well-known example of a banking system.

Thermooptische Effekte in Nd:YAG-Slablasern - Depke, Ralph; Knoke, Stefan; Schöne, Wolfram; Tünnermann, Andreas; Welling, H. (Verhandlungen der Deutschen Physikalischen Gesellschaft)
Vorteile von Laserkristallen in Slab-Geometrie gegenüber Stäben liegen in einer Reduktion der thermisch induzierten Linsenwirkung und der spannungsinduzierten Depolarisation durch einen zick-zack-förmigen Strahlverlauf innerhalb des Kristalls. Durch die Analyse der durch die Anordnung der Pumpquellen und die Dotierungskonzentration bestimmten Temperatur- und Spannungsverteilungen mit Hilfe eines Finite-Element-Modells und die Berechnung der resultierenden optischen Eigenschaften lassen sich die genannten Zielgrößen optimieren. Die Verfahren wurden auf am Laser Zentrum Hannover e.V. entwickelte Nd:YAG-Stab- und Slablaser angewandt und ermöglichten die Entwicklung diodengepumpter Festkörperlaser-Systeme mit Ausgangsleistungen von mehr als 750W bei guter Strahlqualität. Modellerweiterungen unter Berücksichtigung der Wechselwirkung zwischen Lasermoden und aktivem Material werden diskutiert. Diese Arbeit wird gefördert durch das BMBF, FKZ: 13 N 6361

Integrating the Specification Techniques of Graph Transformation and Temporal Logic - Heckel, Reiko; Ehrig, Hartmut; Wolter, Uwe; Corradini, Andrea (Proceedings of the 22nd International Symposium on Mathematical Foundations of Computer Science (MFCS 1997), Bratislava (Slovakia))

Einfrequenzbetrieb von Nd:YAG-Stablasersystemen hoher Ausgangsleistung - Knoke, Stefan; Depke, Ralph; Schöne, Wolfram; Brozek, O.S.; Tünnermann, Andreas; Welling, H. (Verhandlungen der Deutschen Physikalischen Gesellschaft, Weinheim (Germany))

Loose Semantics and Constraints for Graph Transformation Systems - Heckel, Reiko; Ehrig, Hartmut; Wolter, Uwe; Corradini, Andrea

A 2-Categorical Presentation of Distributed Graph Transformation - Gadducci, Fabio; Heckel, Reiko (Proceedings of the Workshop on the General Theory of Graph Transformation Systems (GETGRATS 1997), Bordeaux (France))

Combining Graph Transformations with Temporal Logic - Gadducci, Fabio; Heckel, Reiko; Koch, Manuel (Proceedings of the Workshop on the General Theory of Graph Transformation Systems (GETGRATS 1997), Bordeaux (France))

An Inductive View of Graph Transformation - Gadducci, Fabio; Heckel, Reiko (Proceedings of the 12th International Workshop on Recent Trends in Algebraic Development Techniques (WADT 1997), Tarquinia (Italy))

Compositional Development and Verification of Graph Transformation Systems Based on Views and View Integration - Heckel, Reiko (Proceedings of the Workshop on the General Theory of Graph Transformation Systems (GETGRATS 1997), Bordeaux (France))

Guest Editors' Introduction - Engels, Gregor; Jürgen Schneider, Hans (International Journal on Software Engineering and Knowledge Engineering (IJSEKE))

A Combined Reference Model- and View-Based Approach to System Specification - Engels, Gregor; Heckel, Reiko; Taentzer, Gabriele; Ehrig, Hartmut (Int. Journal of Software and Knowledge Engeneering)
The idea of a combined reference model- and view-based specification approach has been proposed recently in the software engineering community. In this paper we present a specification technique based on graph transformations which supports such a development approach. The use of graphs and graph transformations allows to satisfy the general requirements of an intuitive understanding and the integration of static and dynamic aspects on a well-defined and sound semantical base. On this background, formal notions of view and view relation are developed and the behaviour of views is described by a loose semantics. View relations are shown to preserve the behaviour of views. Moreover, we define a construction for the automatic integration of views which assumes that the dependencies between different views are described by a reference model. The views and the reference model are kept consistent manually, which is the task of a model manager. In case of more than two views more general scenarios are developed and discussed. We are able to show that the automatic view integration is compatible with the loose semantics, i.e., the behaviour of the system model is exactly the integration of the behaviours of the views. All concepts and results are illustrated at the well-known example of a banking system.

Algebraic Approaches to Graph Transformation, Part II: Single Pushout Approach and Comparison with Double Pushout Approach - Ehrig, Hartmut; Heckel, Reiko; Korff, Martin; Löwe, Michael; Ribeiro, Leila; Wagner, Annika; Corradini, Andrea (Handbook of Graph Grammars and Computing by Graph Transformations, Volume 1: Foundations)
The algebraic approaches to graph transformation are based on the concept of gluing of graphs corresponding to pushouts in suitable categories of graphs and graph morphisms. This allows one to give not only an explicit algebraic or set theoretical description of the constructions but also to use concepts and results from category theory in order to build up a rich theory and to give elegant proofs even in complex situations. In the previous chapter we have presented an overview of the basic notions and problems common to the two algebraic approaches the double pushout DPO approach and the single pushout SPO approach and their solutions in the DPO approach. In this chapter we introduce the SPO approach to graph transformation and some of its main results. We study application conditions for graph productions and the transformation of more general structures than graphs in the SPO approach where similar generalizations have been or could be studied also in the DPO approach. Finally we present a detailed comparison of the DPO and the SPO approach especially concerning the solutions to the problems discussed for both approaches in the previous chapter.

How to represent a visual specification - Engels, Gregor; Rekers, Jan; Andries, Marc (Visual Language Theory)

Algebraic Approaches to Graph Transformation, Part I: Basic Concepts and Double Pushout Approach - Corradini, Andrea; Montanari, Ugo; Rossi, Francesca; Ehrig, Hartmut; Heckel, Reiko; Löwe, Michael (Handbook of Graph Grammars and Computing by Graph Transformation, Volume 1: Foundations)
The algebraic approaches to graph transformation are based on the concept of gluing of graphs, modelled by pushouts in suitable categories of graphs and graph morphisms. This allows one not only to give an explicit algebraic or set theoretical description of the constructions, but also to use concepts and results from category theory in order to build up a rich theory and to give elegant proofs even in complex situations. In this chapter we start with an overwiev of the basic notions common to the two algebraic approaches, the double-pushout (DPO) approach and the singlepushout (SPO) approach; next we present the classical theory and some recent development of the double-pushout approach. The next chapter is devoted instead to the single-pushout approach, and it is closed by a comparison between the two approaches.

Special Issue on Graph Transformations

Synchronization of Views and Loose Semantics of Typed Graph Productions - Ehrig, Hartmut; Heckel, Reiko; Padberg, Julia; Taentzer, Gabriele; Wolter, Uwe; Corradini, Andrea; Engels, Gregor (Report on the Dagstuhl-Seminar 9637 on Graph Transformations in Computer Science)
The concept of views is used on two levels. First, so-called design views are developed for structuring specifications, that is, a system is modeled according to different views (e.g., representing the needs of different kinds of users) which have to be synchronized afterwards in order to build the whole system. Views can be specified by means of typed graph transformation systems, where the type graph determines the visible types and the productions describe the known operations of that view. The synchronization of views is done by the construction of cooperative parallel composition of graph transformation systems, developed by Leila Ribeiro and presented at the same seminar. If the specification is complete, a view may describe an observation of the system in operation. In this case we speak of a user view. It turns out that the semantics of such a view cannot be described by computations (i.e., graph transformations), but just by observations of computations of the global system. Such observations of computations cannot be represented by graph transformations in the usual sense because a local view may lack operations (productions) of the global system, so that state changes may be observed that do not have a cause in the local view. Therefore, the notion of graph transition is introduced as loose semantics for productions, where the production specifies only a lower bound to the activities that are to happen during application. Contrastingly, in the classical doublepushout approach to graph rewriting, productions are interpreted as complete descriptions of the transformations to be performed. For typed graph transformation systems a transition sequence semantics is developed, comprising all finite and infinite sequences of transitions in a system. Moreover, this semantics is shown to be compositional w.r.t. the synchronization of views.

Behavioral Constraints for Loose Graph Transformation Systems - Heckel, Reiko (Report on the Dagstuhl-Seminar 9637 on Graph Transformations in Computer Science)

Industrial maintenance modelled in SOCCA: an experience report - de Bunje, Tineke; Engels, Gregor; Groenewegen, Luuk; Matsinger, Aart; Rijnbeek, Martin (Proceedings of the Fourth International Conference on the Software Process (ICSP 1996), Brighton (UK))
A large industrial process, software maintenance, has been modelled by using the process modelling language SOCCA. The paper reports about the experiences with this trial. In particular, feasibility, expressiveness, quality and the overall benefits of a formal SOCCA model are discussed and compared to the formerly existing informal process description. In order to illustrate the results, a well chosen process model fragment from the larger model is outlined in detail. It addresses in particular the human-intensive cooperation within the process and shows the seamless combination of technical components and human agent components in the SOCCA model. The main conclusions from this trial are that formal SOCCA models are suited to model realistic industrial processes and that due to an intrinsic modular structure of a SOCCA model, even huge models remain reasonably readable and understandable

A View-Based Approach to System Modelling - Engels, Gregor; Ehrig, Hartmut; Heckel, Reiko; Taentzer, Gabriele; Corradini, Andrea (Report on Dagstuhl-Seminar 9637 on Graph Transformations in Computer Science)
In order to manage the complexity of large system specifications, they have to be decomposed into subspecifications. Each subspecification describes a certain part of the system. This might be a certain aspect, like the data, dynamic, or functional aspect, as it is known from object-oriented modelling techniques. Or it might be a certain view onto the system, as it is known from database modelling techniques. The talk motivates the usage of views in graph grammarbased specifications. First, the usage of typed graph grammars inherently ensures an integration of the data and the functional aspect within a view. Second, it is explained that it is not appropriate in case of views to have a fixed semantics. The standard fixed semantics, i.e. a graph transformation system, has to be relaxed to a loose semantics, i.e. a graph transition system. This reflects the idea that a view models only a part of the complete system. Other views may overlap a view with respect to data or functionality. A complete system specification is yielded by exploiting the approach of cooperative parallel composition of graph grammars (see talk by Leila Ribeiro).

Object-oriented specification of coordinated collaboration - Engels, Gregor; Groenewegen, Luuk; Kappel, Gerti (Proceedings of IFIP World Conference on IT Tools (1996), Canberra (Australia))
Object-oriented specification mechanisms have become famous for modelling structure and behaviour together in terms of autonomous objects communicating via message passing. However, whereas most object-oriented specification methods are strong in modelling the local behaviour of single objects, they fall short on modelling the coordinated behaviour and collaboration of several objects together The aim of this paper is to contribute to fill this gap. The paper reports on concepts, language constructs, and experiences with three collaboration formalisms in the area of object-oriented specifications.

Graph Transformation for Specification and Programming - Andries, Marc; Engels, Gregor; Habel, Annegret; Hoffmann, Berthold; Kreowski, Hans-Jörg; Kuske, Sabine; Plump, Detlef; Schürr, Andy; Taentzer, Gabriele
The framework of graph transformation combines the potentials and advantages of both, graphs and rules, into a single computational paradigm. In this paper we survey recent developments in applying graph transformation as a rule-based framework for the specification and development of systems, languages, and tools. After presenting the basic features of graph transformation, we discuss a spectrum of applications including the evaluation of functional expressions, the specification of an interactive graphical tool, an example specification for abstract data types, and the definition of a visual database query language. The case studies indicate the need for a graph transformation language that provides suitable structuring principles and is independent of a particular graph transformation approach. To this end, we sketch the basic features of the new graph- and rule-centered language Grace, currently under development, that permits systematic and structured specification and programming based on graph transformation.

Definition of an Encapsulated Hierarchical Graph Data Model: Static Aspects, Part 1. - Busatto, Giorgio; Engels, Gregor

Object-oriented Specification of Coordinated Collaboration - Engels, Gregor; Groenewegen, Luuk; Kappel, Gerti

Horizontal and Vertical Structuring of Typed Graph Transformation Systems - Heckel, Reiko; Corradini, Andrea; Ehrig, Hartmut; Löwe, Michael

Towards Measurable Process Models - de Bunje, Tineke; Engels, Gregor; Groenewegen, Luuk; Heus, Michael; Matsinger, Aart (Proceedings of the Workshop on Software Process Technology (EWSPT 1996), Nancy (France))

Pragmatic and Semantic Aspects of a Module Concept for Graph Transformation Systems - Ehrig, Hartmut; Engels, Gregor (Selected papers from the 5th International Workshop on Graph Gramars and Their Application to Computer Science, Williamsburg, VA (USA))
The paper presents a conceptual framework for a module concept for graph transformation systems from a software engineering as well as from a theoretical point of view. The basic idea is to reuse concepts, which are known within or without the graph grammar field, to structure large specifications. These are the concept of distributed graph transformation systems, the concept of inheritance of specifications, and the import-export-interface concept. All these concepts are presented in a uniform framework based on the syntactical notion of a graph class specification and its semantics given by a graph transformation system. This is the basis for an explicit integration of these concepts and a corresponding specification language, to be discussed in a subsequent paper.

Comprehensive Support for Change: Generic, Multi-dimensional (Software) Engineering Frameworks (position paper) - Engels, Gregor; Zamperoni, Andreas (Proceedings of the Workshop on Requirements Engineering in a Changing World (satellite event of the Conference on Advanced Information Systems Engineering (CAISE 1996)), Crete (Greece))

Reuse of Software Process Fragments is Reuse of Software, too - Groenewegen, Luuk; Engels, Gregor (Proceedings of the 10th International Software Process Workshop (ISPW 1996), Ventron (France))
By means of a special sofnvare process model component we have been successful in specifring somare process model evolution, This component also handles much reuse of software process model fragments. To handle the reuse of the software as it is being produced by a software process, another extra component can be added to the model for that software process. It is argued why this extra component is comparable to the special component for evolution.

Automatic Integration of Safety Invariants into Z Specifications - Heckel, Reiko; Conrad, Mirko; Egger, Gottfried; Hiemer, Jörg (Proceedings of the Workshop on Tools for System Development and Verifcation)
This extended abstract describes a mechanism to automatically incorporate safety requirements into operational specifications written in Z. For every individual operation the global (i.e. operation independent) safety invariants are transformed into a predicate which is used to extend the original precondiction of the operation. The operation constructed this way shows the same beavior as the original one whenever its post state satisfies the invariant. Otherwise it refuses to do anything. The construction of the precondition can be carried out automatically and a corresponding tool development is in progress.

Graph Grammars with Negative Application Conditions - Habel, Annegret; Heckel, Reiko; Taentzer, Gabriele (Fundamenta Informaticae)

Horizontal and Vertical Structuring of Typed Graph Transformation Systems - Heckel, Reiko; Corradini, Andrea; Ehrig, Hartmut; Löwe, Michael (Mathematical Structures in Computer Science)

A Hybrid Query Language for the Extended Entity Relationship Model - Andries, Marc; Engels, Gregor (Journal of Visual Languages and Computing)
We present the hybrid query language HQL/EER for an Extended Entity-Relationship model. As its main characteristic, this language allows a user to usebothgraphical and textual elements in the formulation of one and the same query. We demonstrate the look-and-feel of this query language by means of examples, and show how syntax and semantics of this language are formally defined using programmed graph rewriting systems. Although we present the language in the context of the EER model, the concept of hybrid languages is applicable in the context of other database models as well. We illustrate this claim by discussing a prototype implementation of a Hybrid Query Tool based on an object-oriented approach, namely the Object Modeling Technique (OMT).

Tight Integration on One Document: The Programming Environment - Engels, Gregor; Nagl, Manfred; Schäfer, Wilhelm; Westfechtel, Bernhard (Building Tightly Integrated Software Development Environments: The IPSEN Approach)

Attributed Graph Transformations with Controlled Application of Rules - Heckel, Reiko; Müller, Jürgen; Taentzer, Gabriele; Wagner, Annika (Proceedings of the Colloquium on Graph Transformation and its Application in Computer Science)
We present a combination of recent extensions to single-pushout graph transformations, as there are attribution, application conditions and amalgamated graph transformations and add a simple transaction concept on top of this formalism. Thereby, we provide the formal basis for several examples, where these concepts are used in combination.

Record Linkage of Anonymous Data by Control Numbers - Thoben, Wilfried; Appelrath, Hans-Jürgen; Sauer, Stefan (Proceedings of the 18th Annual Conference of the Gesellschaft für Klassifikation, Oldenburg (Germany))

Embedding of Conditional Graph Transformations - Heckel, Reiko (Proceedings of the Colloquium on Graph Transformation and its Application in Computer Science)
Single pushout graph transformations at injective matches are extended by negative application conditions. It is shown, how right-sided application conditions can be transformed into equivalent left-sided ones. Based on this result, conditional derived rules are introduced and a theorem, similiar to the double pushout embedding theorem is shown. Finally, three variants of contextual application conditions are discussed with respect to their expressive power and expected results.

Graphische Spezifikation ausgewählter Teile von AGG - einem algebraischen Graphgrammatiksystem - Conrad, Mirko; Gajewsky, Magdalena; Holl-Biniasz, Rainer; Rudolf, Michael; Demuth, Jochen; Weber, Stephan; Heckel, Reiko; Müller, Jürgen; Taentzer, Gabriele; Wagner, Annika

Specialization of Object Life Cycle Definitions - Ebert, Jürgen; Engels, Gregor
Several object-oriented modeling approaches propose to describe the dynamic behaviour of objects by state transition diagrams. None of them provides precise rules or conditions for the interrelation between the behaviour description of classes and those of their subclasses. In this paper, we discuss this interrelation in detail. It turns out that one has to distinguish between the observable and the invocable behaviour of objects and that different compatibility requirements between the diagrams exist depending on the type of behaviour.

Encapsulated Hierarchical Graphs, Graph Types, and Meta Types - Engels, Gregor; Schürr, Andy

Coordination by Behavioural Views and Communication Patterns - Groenewegen, Luuk; Engels, Gregor (Proceedings of the 4th European Workshop on Software Process Technology (EWSPT 1995), Noordwijkerhout (The Netherlands))

A Compositional Approach to Structuring and Refinement of Typed Graph Grammars - Corradini, Andrea; Heckel, Reiko (Proceedings of the Joint COMPUGRAPH/SEMAGRAPH Workshop on Graph Rewriting and Computation (SEGRAGRA 1995), Volterra (Italy))
Based on a categorical semantics that has been developed for typed graph grammars we uses colimits (pushouts) to model composition and (reverse) graph grammar morphisms to describe refinements of typed graph grammars. Composition of graph grammars w.r.t. common subgrammars is shown to be compatible with the semantics, i.e. the semantics of the composed grammar is obtained as the composition of the semantics of the component grammars. Moreover, the structure of a composed grammar is preserved during a refinement step in the sense that compatible refinements of the components induce a refinement of the composition. The concepts and results are illustrated by an example.

GRAPHIT: Graphical Support and Integration of Formal and Semiformal Methods for Software Specification and Development - Bardohl, Bernhard; Bardohl, Roswitha; Castro, Paulo; Ehrig, Hartmut; Heckel, Reiko; Ribeiro, Leila; Nunes, Daltro; Martini, Alfio (Proceedings of the 3rd German-Brazilian Workshop on Information Technology (1995), Berlin (Germany))
The overall aim of this paper is a proposal how to bridge the gap between formal specification techniques developed in research projects and semi--formal or informal specifications used in industrial practice. The main idea to overcome these problems is to develop graphical support for formal methods in order to increase acceptance by practitioners and to provide means for integration of formal and semi--formal methods. More specifically suitable concepts will be developed to combine algebraic specifications, Petri Nets, and Graph Grammars with each other and with distinguished graphical components to be used by industrial partners.

Encapsulated Hierarchical Graphs, Graph Types, and Meta Types - Engels, Gregor; Schürr, Andy (Proceedings of the Joint COMPUGRAPH/SEMAGRAPH Workshop on Graph Rewriting and Computation (SEGRAGRA 1995), Volterra (Italy))
Currently existing graph grammar-based specification languages have serious problems with supporting any kind of “specification-in-the-large” activities. More precisely, they have deficiencies with respect to modeling hierarchical data structures or specifying meta activities like manipulation of graph schemata. Furthermore, already proposed graph grammar module concepts are still too abstract to be useful in practice. Our contribution addresses these problems by introducing a new hierarchical graph data model with an infinite number of schema, meta-schema, etc. layers. It forms the base for a forthcoming concrete modular graph grammar specification language where in addition information hiding aspects like explicit export and import interfaces are expressible.

Ensuring Consistency of Conditional Graph Grammars - A constructive Approach - Heckel, Reiko; Wagner, Annika (Proceedings of the Joint COMPUGRAPH/SEMAGRAPH Workshop on Graph Rewriting and Computation (SEGRAGRA 1995), Volterra (Italy))

Fundamentals of Object-Oriented Languages, Systems, and Methods
During the last decades there has been progress within the object-oriented community in agreeing on what object- orientedness means. The role of object identity, specialization, inheritance, and dynamic binding have been examined. However, a careful look at articles written by people with a theory, programming language, database, and software engineering background shows that the semantical understanding of the same features still differs considerably. A well-known example is the feature of inheritance, which has quite a different meaning for persons from the database comunity with a semantic data model background and persons form the programming language community with a compiling technique background This observation also applies to the literaute on object-oriented software development methods. Here, object -oriented analysis and design methods are often heavily influenced by semantic data modelling consepts- An implemantion of an object-orinted design by an objeckt-oriented progamming language usually causes more difficulties than expected although the "same" object-oriente paradigm is used...

Graph Gramars and Their Application to Computer Science, 5th International Workshop (1994), Selected Papers

Berücksichtigung von Datenschutzaspekten in einem bevölkerungsbezogenen Krebsregister - Thoben, Wilfried; Appelrath, Hans-Jürgen; Rettig, Jens; Sauer, Stefan (Proceedings of the conference on Medizin und Information, Biometrie und Epidemiologie (GMDS 1994), Dresden (Germany))
Die Pilotphase 1993/ 94 zum Aufbau eines Niedersächsischen Krebsregister untersucht das im Entwurf des Bundeskrebsregistergesetzes vorgesehen Modell für ein bevölkerungsbezogenes Krebsregister. Darin werden die Krebsmeldungen in einer Vertrauensstelle erfaßt und die personenidentifizierenden Daten vor der Übermittlung an die Registerstelle anonymisiert, wo sie dann zu einem bevölkerungsbezogenen Krebsregister verdichtet und epidemiologischer Forschung zur Verfügung gestellt werden ([1], [2], [3]). Dieses sogenannte „Michaelis“-Modell erlaubt eine bevölkerungsbezogene Registrierung von Krebsfällen unter Berücksichtigung datenschutzrechtlicher Aspekte („Informationelles Selbstbestimmungsrecht“) der einzelnen Betroffenen. In vier Teilprojekten werden dabei in der Modellregion Weser-Ems die Integration krebsregistrierender Einrichtungen, die Chiffrierung/ Dechiffrierung von Krebsmeldungen, der Abgleich anonymisierter Meldungen in der Registerstelle und die Entwicklung eines epidemiologischen Informationssystem betrachtet ([4], [5]).

Structural and Behavioural Views on OMT-Classes - Ebert, Jürgen; Engels, Gregor (Proceedings of the International Symposium on Object-Oriented Methodologies and Systems (ISOOMS 1994), Palermo (Italy))
Object-oriented specification languages provide means to specify the static structure, as well as the allowed dynamic behaviour of objects. Here, the dynamic behaviour is usually described by giving the methods and a state transition diagram which defines the allowed sequences of methods on objects of a certain class. Specialized classes are defined using the inheritance relationship. In order to enable reusability while guaranteeing type substitutability, subclass specifications have to be compatible with respect to static and dynamic aspects with their corresponding superclass specifications. Classes have to provide a large shopping list of operations to satisfy the needs of all possible users. The interests of specific users are often restricted to a subset of operations and thus to a restricted behaviour. This paper describes a formalization of class descriptions given by attributes, operations, as well as state transition diagrams. It defines compatibility between sub- and superclasses and introduces the notion of views in the sense of hiding parts of a class description. It turns out that a view has the same properties as a (virtual) superclass.

Object-Oriented System Development: Will the New Approach Solve Old Problems? - Engels, Gregor; Kappel, Gerti (Proceedings of the IFIP 13th World Computer Congress on Information Processing, Hamburg (Germany))
Object-oriented system development is wideley recognized as improving productivity and reducing system maintenance costs. However, existing approaches have not sufficiently addressed the following three questions which are equally important to users and researchers. Firstly, what are the benefits of object-oriented system development compared to traditional approaches? Secondly, what are the essential features of an objectoriented life cycle model to fulfill the benefits of object-oriented development? And thirdly, what are the pitfalls of object-oriented development and how to cope with them? The paper investigates answers to all three questions in concert.

Towards a Module Concept for Graph Transformation Systems: The Software Engineering Perspective - Engels, Gregor; Ehrig, Hartmut (Proceedings Colloquium on Graph Transformation and its Application in Computer Science)